Screening of poly vinyl chloride degrading bacteria from plastic contaminated area of Baddi - Kumar, Sahni; Teotia, U. V. S; Singh, Yogendra (Creative Pharma Assent, 2017)
Plastic wastes are posing ever increasing environmental concerns. Recent research works have shown that most of the constituents of plastics can be degraded by microbes and the film plastics can be treated by microbial systems. In this study, poly vinyl chloride (PVC), degrading bacteria’s were isolate and characterize from soil dumped with plastics. The PVC degradating bacterial were identified as E.Coli, Staphylococcus, Pseudomonas and Klebsiella. It was observed that maximum degradation by Pseudomonas and degradation after 10 months was 40.53%, 23.06%, 10.92% and 5.32% for Pseudomonas, Klebsiella, Staphylococcus and E.Coli respectively.This work concluded that soil contains bacteria’s that have ability to carry degradation of poly vinyl chloride (PVC)